The Influence of The Audiovisual Application of MKJP Contraceptive on Knowledge and Decision-Making of MKJP Contraceptive in The Technical Implementation Unit of The Tering Seberang West Kutai Community Health Center - Faridah, Faridah; Corniawati, Inda; Dwi Utami, Kurniati (Rifa'Institute, 2023)
Introduction: Indonesia is the 5th country in the world, efforts to reduce the birth rate (TFR) in Indonesia are carried out through the national Family Planning movement to prevent mortality due to pregnancy and childbirth due to unplanned pregnancies so it is necessary to increase the use of MKJP family planning through counseling using media The right one is audiovisual. Objective: The purpose of this study was to determine the effect of implementing MKJP family planning audiovisuals on knowledge and decision making on MKJP family planning decisions. Methods: This type of research is a quasi-experimental design with one group pretest – posttest design. Results and Discussion: Knowledge of MKJP Contraceptive in post partum mothers before the application of audiovisual as much as 66.7% had less knowledge and after applying audiovisual as much as 77.8% had good knowledge. The use of audiovisual containing MKJP family planning materials makes it easier for mothers to understand about MKJP family planning materials so that with the understanding they have, they decide to use one of the MKJP family planning materials voluntarily without coercion. Conclusion: the application of audiovisuals about MKJP Contraceptive to knowledge and decision making about MKJP Contraceptive.